2018
DOI: 10.4103/ija.ija_39_18
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic management and perioperative outcomes of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy: A retrospective analysis

Abstract: Background and Aims:Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) is becoming the standard treatment option for peritoneal carcinomatosis but is associated with high rates of morbidity and mortality. Our aim was to retrospectively analyse and evaluate intra-operative factors associated with morbidity and mortality of CRS and HIPEC.Methods:Intra-operative data were collected for cases done over 1 year (24 cases) and analysed for the primary outcome of post-operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
22
0
2
Order By: Relevance
“…[ 17 ] The fluid management was guided by non-invasive continuous cardiac output monitoring with FloTrac in patients with high tumour load and patient having persistent haemodynamic perturbations in the study being published. [ 10 ] Another randomised controlled trial which studied various outcomes related to CRS and HIPEC reported that the use of a goal-directed fluid therapy using the FloTrac/Vigileo was associated with improved patient-related outcome for major abdominal and systemic post-operative complications and reduced length of hospital stay. [ 18 ] The less-invasive haemodynamic monitoring devices such as the oesophageal Doppler may be useful; however, the tool and its utility though proven in other surgical interventions but has not been assessed in CRS and HIPEC.…”
Section: Fluid Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 17 ] The fluid management was guided by non-invasive continuous cardiac output monitoring with FloTrac in patients with high tumour load and patient having persistent haemodynamic perturbations in the study being published. [ 10 ] Another randomised controlled trial which studied various outcomes related to CRS and HIPEC reported that the use of a goal-directed fluid therapy using the FloTrac/Vigileo was associated with improved patient-related outcome for major abdominal and systemic post-operative complications and reduced length of hospital stay. [ 18 ] The less-invasive haemodynamic monitoring devices such as the oesophageal Doppler may be useful; however, the tool and its utility though proven in other surgical interventions but has not been assessed in CRS and HIPEC.…”
Section: Fluid Managementmentioning
confidence: 99%
“…A balanced fluid management protocol would maintain colloid oncotic pressure and urinary output. [ 10 ] Colloids replenish intravascular volume in a ratio of 1:1 in a fluid responsive patient and may be used to maintain Optovolaemia. Such surgeries lead to protein loss owing to ascites drainage and extensive tissue handling and cytoreduction.…”
Section: Fluid Managementmentioning
confidence: 99%
See 3 more Smart Citations